Non-Invasive Assessment and Evaluation of Portal Hypertension in Patients with Liver Cirrhosis - Indra Marki; Rino Alvani Gani; Marcellus Simadibrata; Chudahman Manan (The Indonesian Society for Digestive Endoscopy, 2001)
Ultrasonography examination is an one of examination that can be used to see the abnormality of portal vein system. The technology of ultrasonography examination has further developed especially after using of Doppler ultrasonography which could portray haemodynamic changes from portal vein in liver cirrhosis patient. From this examination we also could predict bleeding. Keywords: liver cirrhosis, portal hypertension, doppler ultrasonography